Performance Analysis on Wireless Sensor Network Based on Zigbee Wireless Communication Protocol - Agustini Rodiah Machdi; Yamato Tan (JREC (Journal of Electrical and Electronics), 2021)
This journal discusses the performance analysis of a Wireless Sensor Network (WSN) system based on the Zigbee Wireless Communication protocol. Zigbee in this system is used for sensor communications that do not require high data transmission speeds, such as sensor applications, such as temperature, humidity, light, pressure, and other sensors. The analysis carried out is to examine the QoS of a network system based on the topology used in the Zigbee protocol-based WSN system. The results of the study show that the use of topology is very influential on the availability, stable speed, and accuracy of the data transmitted between these sensors.